Mesenchymal Stem/Stromal Cell-Mediated Mitochondrial Transfer and the Therapeutic Potential in Treatment of Neurological Diseases - Deqiang Han; Xin Zheng; Xueyao Wang; Tao Jin; Li Cui; Zhiguo Chen (Hindawi Limited, 2020)
Mesenchymal stem/stromal cells (MSCs) are multipotent stem cells that can be derived from various tissues. Due to their regenerative and immunomodulatory properties, MSCs have been extensively researched and tested for treatment of different diseases/indications. One mechanism that MSCs exert functions is through the transfer of mitochondria, a key player involved in many biological processes in health and disease. Mitochondria transfer is bidirectional and has an impact on both donor and recipient cells. In this review, we discussed how MSC-mediated mitochondrial transfer may affect cellular metabolism, survival, proliferation, and differentiation; how this process influences inflammatory processes; and what is the molecular machinery that mediates mitochondrial transfer. In the end, we summarized recent advances in preclinical research and clinical trials for the treatment of stroke and spinal cord injury, through application of MSCs and/or MSC-derived mitochondria.